Inovasi Pendidikan Pesantren (Metode Kombinasi Pembelajaran Keislaman di Pesantren Al-Ihsan) - Dede Dendi (Fahima, 2023)
Islam is a dynamic religion that upholds education. Islamic education requires the perpetrators to be able to instill Islamic values in every step. Islamic education opens work and innovation to continue to make new things in developing education. This research is about the study of Islamic education innovation conducted at the Al-Ihsan Cibiru Islamic Boarding School, Bandung. The purpose of this study is to photograph and find out the educational sistem that combines traditional, modern, and contemporary methods in non-formal Islamic boarding schools. The method uses qualitative research methods can be defined as research procedures that produce descriptive data in the form of written or spoken words from people and observable behavior. The results of this study state that the Al-Ihsan Islamic boarding school in carrying out educational and teaching activities uses a combination of classical, modern, and contemporary methods. The application of this combination method helps to strengthen Islamic teachings with the classical pesantren tradition but is not rigid but is even adaptive, reactive, and accommodating to general knowledge. So that the output of the pesantren gives birth to Muslim intellectuals who have a wealth of classical literacy and open-mindedness.